Separation and activity standardization of 226Ra by 4πα liquid scintillation counting - Bluďovský, Richard; Suková, Vlasta (Applied radiation and isotopes, 2022)
The 226Ra standardization method is based on the removal of 222Rn by intensive venting and subsequent separation of radon daughter decay products on a column packed with lead filings, 226Ra remains in the eluate. The eluate was repeatedly measured by LSC, and the measured values were corrected for the increase in the activity of the 226Ra daughter products since the separation was completed. The method was applied to EB type solutions from CMI production. The 226Ra activity was determined with an uncertainty better than 0.6.
Keywords: referenční standardy; Reference Standards; Radium; 4πα liquid scintillation counting; dceřiné produkty radonu; Radon Daughters; Scintillation Counting; scintilace - počítání; radium; radon; Radon; Water Pollutants, Radioactive; (226)Ra standardization; (226)Ra separation; radioaktivní látky znečišťující vodu